Normal high velocity solid dust impacts on tiles of tokamak-relevant temperature - Marco De Angeli; Panagiotis Tolias; Francisco Suzuki-Vidal; Dario Ripamonti; Tim Ringrose; Hugo Doyle; Giambattista Daminelli; Jay Shadbolt; Peter Jarvis; Monica De Angeli (Nuclear Materials and Energy)
Runaway electron incidence on plasma facing components triggers explosive events that are accompanied by the expulsion of fast solid debris. Subsequent dust-wall high speed impacts constitute a mechanism of wall damage and dust destruction. Empirical damage laws that can be employed for erosion estimates are based on room-temperature impact experiments. We use light-gas gun shooting systems to accelerate solid tungsten dust to near-supersonic speeds towards bulk tungsten targets that are maintained at different temperatures. This concerns targets cooled down to −100°C with liquid nitrogen and targets resistively heated up to 400 °C. Post-mortem surface analysis reveals that the three erosion regimes (plastic deformation, bonding, partial disintegration) weakly depend on the target temperature within the investigated range. It is concluded that empirical damage laws based on room-temperature measurements can be safely employed for predictions.